2022
DOI: 10.3390/jcm11030520
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis in Ischemic Stroke Patients: Case Definition Challenges of the New Classification Scheme (2018)

Abstract: The identification of the associative relationships between ischemic stroke (IS) and risk factors such as advanced age and periodontitis is essential to design real screening protocols and to address them using primary and secondary preventive policies. This study primarily aimed to evaluate the diagnostic performance of the 2018 European Federation of Periodontology/American Academy of Periodontology (EFP/AAP) case definition in detecting periodontitis against the 2012 Centers for Disease Control and Preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
(102 reference statements)
2
8
0
Order By: Relevance
“…This trend of reclassifying patients has already been reported by our team, with a misclassification rate of 23.41% ( n = 33) found among a group of stroke patients [ 7 ]. In the present study, higher rates of misclassification of periodontal conditions were identified, namely, 39.6% ( n = 21) for the SSc group and 31.1% ( n = 33) for the controls.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This trend of reclassifying patients has already been reported by our team, with a misclassification rate of 23.41% ( n = 33) found among a group of stroke patients [ 7 ]. In the present study, higher rates of misclassification of periodontal conditions were identified, namely, 39.6% ( n = 21) for the SSc group and 31.1% ( n = 33) for the controls.…”
Section: Discussionsupporting
confidence: 79%
“…Periodontitis is a chronic infectious inflammatory disease of the tooth-supporting apparatus frequently reported in the general population [ 4 ], as well as in some systemically affected groups [ 5 , 6 , 7 , 8 ]. Periodontitis has been epidemiologically associated with various chronic diseases, such as cardiovascular diseases, type 2 diabetes mellitus, certain cancers, inflammatory bowel disease, and rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators were previously calibrated at the initiation of another study [ 31 ]. At the initiation of the present study, the investigators received written instructions on the study protocol and participated in two training meetings coordinated by a senior periodontist (D.R.).…”
Section: Methodsmentioning
confidence: 99%
“…However, the cause of CAL is not specifically described in the NHANES periodontitis database. Therefore, analysis of NHANES data using the 2018 EFP/AAP classification of periodontal diseases may increase the prevalence of periodontitis [50,51]. CAL and periodontal PD were used in the 2012 AAP/ CDC periodontitis case definition, minimizing the potential erroneous effect of periodontal recession on the accuracy of probing depth measurements [47].…”
Section: Plos Onementioning
confidence: 99%